Advanced Composites and Hybrid Materials - McNally, Tony.; Guo, John Zhanhu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Advanced Composites and Hybrid Materials provides an international interdisciplinary platform for rapid scientific communication among materials scientists, engineers, chemists, biologists, and physicists working on composites and, in particular, nanocomposites. The journal publishes top-level research on materials design, surface and interface science/engineering, manufacturing, structure control, property design, and device fabrication and other applications as well as related simulation/modeling studies. Papers on the relationship between the fillers and the matrix are of particular interest. The journal encompasses polymer, metal, and ceramic matrices, with particular interest in reviews and meta-analyses on materials selection. Coverage includes transport properties; strategies for controlling interfaces and composition distribution; bottom-up assembly of nanocomposites; highly porous and high-density composites; electronic structure design; materials synergisms; and thermoelectric materials. Advanced Composites and Hybrid Materials is a single-blind peer reviewed journal.
Keywords: Ceramic materials; Materials; Polymers; Ceramics; Materials Engineering; Polymers